Elimination of Oil Residual inside the Copper Pipe Using Ladder Technique - Witsarut Sriratana; Riichi Murayama (My University, 2013)
This study presents the methodology to eliminate oil residual in copper pipe due to rolling process for manufacturing coil used in air conditioner. The pressure caused by Nitrogen flow rate was applied starting from 0, 5, 10, and 15 bar, respectively which was depending on time delay and pipe length. The developed system was divided into 2 modules: Parallel pressure ladder module (PPLM) [1] and Serial pressure ladder module (SPLM) which were experimented with 2 sizes of copper pipe: diameter 7.29 mm, thickness 0.25 mm, and length 10 km, and diameter 8 mm, thickness 0.25 mm, and length 10 km. From experiment, it can be noted that PPLM would perform better in elimination of oil residual compared to SPLM. About 97.44% (0.04 mg/m) and 97.59% (0.05 mg/m) of oil residual can be respectively eliminated from diameter 7.29 mm pipe and diameter 8 mm pipe which exceeded the standard allowance of 30% or 0.1 mg/m. Moreover, the cost of Nitrogen can be reduced by 6.25% per month.
Keywords: Allowance (engineering); Residual oil; Bar (unit); Solar Thermal and Photovoltaic Systems